Out of the shadows: non-communicable diseases and palliative care in Africa. Issue 2 (21st September 2015) - Powell, R A; Ali, Z; Luyirika, E; Harding, R; Radbruch, L; Mwangi-Powell, F N
Abstract : Non-communicable diseases (NCDs) in Africa have been comparatively neglected, partly due to donor-driven funding priorities. This is despite NCDs being the principal cause of mortality globally, with the majority incidence occurring in low-income and middle-income nations. Most of the patients with NCDs will suffer from pain, breathlessness and other physical symptoms, or need support with psychosocial or spiritual problems. Reflecting regional disease prevalence, late-stage clinical presentation, limited funding and restricted access to curative therapies, palliative care need in Africa is significantly high. Although palliative care provision has advanced significantly on the continent in the past decade, much of this development was driven by services for adult HIV patients. However, recent international and regional political declarations and commitments constitute a new global NCD agenda that calls for the integration of palliative care into the NCD response. This could be achieved under a chronic care model of service provision in partnership with other clinical providers in an integrated care continuum spanning prevention, early detection, diagnosis, treatment, survivorship and the end of life. Four important challenges have to be addressed if palliative care is to contribute meaningfully to this NCD agenda: (1) existing variation in the ability of countries to deal with NCDs per se; (2) ensuring clinical partners are integrated effectively with palliative care; (3) agreeing implementation is linked to relevant national-level and patient-level metrics; and (iv) underpinning palliative care and NCD care with a rigorous and locally relevant evidence base demonstrating appropriate, feasible and effective care.